Diffusion and system impact of residential battery storage under different regulatory settings - Daniel Fett; Christoph Fraunholz; Dogan Keles (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2021)
Cost reductions of rooftop photovoltaics and battery storage, increasing retail electricity prices as well as falling feed-in remuneration provide strong incentives for many German households to engage in self-consumption. These developments may also affect the electricity system as a whole. Against this background, we jointly apply a prosumer simulation and an agent-based electricity market simulation in order to investigate the long-term impacts of a residential battery storage diffusion on the electricity market. We analyze different regulatory frameworks and find significant effects on the household level, yet only moderate system impacts. In the long run, the diffusion of residential battery storage seems difficult to govern, even under a restrictive regulation. In contrast, the way the batteries are operated may be easier to regulate. Policymakers and regulators should focus on this aspect, since a system-friendly battery operation supports the system integration of residential photovoltaics while having little impact on the households' selfsufficiency.
Keywords: 330; Self-consumption; Battery storage; Technology diffusion; Electricity system; Agent-based simulation; Model coupling